Identification of microbial composition of Swedish hard cheese by MALDI ToF mass spectrometry - Dissanayake, R.G. Thilini Nuwandhara (2018)
This study was done with four different Swedish cheese samples in terms of cheese variety, brand and sensorial properties. The objectives of the current study were to identify the different microorganisms present in the Swedish hard cheese by matrix assisted laser desorption ionization-time of flight mass spectrometry (MALDI ToF MS) and to test the suitability of the method to be use for cheese. And also, to iden-tify differences between good and bad sensorial quality hard cheese in terms of microbial composition. Four different cheese samples were cultivated on four dif-ferent agar media under both aerobic and anaerobic conditions and the resulted colonies were identified by MALDI ToF MS. This technique allows to identify most of the bacteria only up to species level due to the limitation of database on subspecies and strains levels and some of the microorganisms stayed unidentified. The log colony forming units per gram of cheese was not significantly different among cheese A-good, A-bad, B and C. However, the microbial composition was different for all studied cheese samples. Also, the good and bad sensory quality cheeses were significantly different in terms of microbial composition and the method can be considered as the first tool for deeper investigation of cheese micro-biota.